Penanaman Pendidikan Karakter Religius di Lembaga Pendidikan MI Nurul Yaqin Surabaya - Ixfina, Ficky Dewi; Soleha (Tarsib: Jurnal Program Studi PGMI, 2023)
The main focus of the research is to understand the extent to which religious character education programs have been implemented and have an influence in students' daily lives. The research method used is descriptive qualitative research using interview techniques, observation and documentation. The research results show that the religious character education program at MI Nurul Yaqin Surabaya has been well structured and is running smoothly, but there is still room for improvement and adjustments to increase its effectiveness. As a follow-up, it is recommended that madrasas continue to carry out regular evaluations of religious character education programs, hold training for teachers regarding more effective implementation, and increase parent participation in supporting religious character education at home and school. In this way, MI Nurul Yaqin can ensure that its religious character education program achieves the expected goals and has a positive impact on overall student development.